Quantitative analysis of passive seasonal cold storage with a two-phase closed thermosyphon. (15th February 2020) - Li, Xingping; Li, Ji; Zhou, Guohui; Lv, Lucang
Highlights: Icing process through a thermosyphon was visualized for three years. The parameters affecting cold energy storage were studied in detail. Cold energy stored was quantified theoretically and verified experimentally. Energy conservation for agricultural products storage warehouse was calculated. This study provides guidance for passive seasonal cold storage system. Abstract: Seasonal cold energy storage is an efficient and sustainable technique for energy acquisition that stores environmental cold energy in winter and offers free cooling in industries, such as food storage or data center cooling. This paper presents a visualized seasonal cold storage system utilizing a two-phase closed thermosyphon as the passive heat-transfer device. Meanwhile, a theoretical model of energy conservation for the passive cold energy storage system was established. The process of ice formation was quantitatively studied through water/ice temperature variations and icicle shape evolution. The effects of the ambient variables and the working period of a thermosyphon on the ice formation were identified. Finally, a conceptual passive cold storage warehouse based on our validated model was proposed and compared with a traditional warehouse cooled by air conditioning system in terms of energy conservation and benefit-cost ratio. This study provides a practical guidance for passive cold storage system design and performance evaluation.